Application of a personal Santini technique in the resolution of a complex celiac trunk aneurysm - endovascular treatment - Gianpaolo Santini; Pasquale Quassone; Luca Tarotto; Francesco Arienzo; Giuseppe Sarti (Medicinski glasnik, 2020)
Aim: Vascular pathologies have been already explored for the most of their aspects. It is a group of pathologies with unclear ethology and with an evolution in time not easy to forecast. Treatment guidelines are conflicting. The aim of this study was to describe cases in their most practical and technical aspect, especially in complicated conditions. Methods: This was a descriptive case report of a patient with a hepatic artery aneurysm complicated by a dissection leading up to the splenic artery, and how the team had invented a planned treatment for the patient using a minimally invasive approach. The experience was born with the intention of showing how the endovascular approach is at least as safe as the traditional one despite the complexity of our case. Results: The procedure was completed without any complications. After a stay in long day surgery, the patient returned home. Conclusion: Using a minimally invasive technique allows to reduce the patient's post-operative suffering and the economic burden on the health system.
Keywords: aneurism; dissection; endovascular; hepatic artery; splenic artery